Silk‐Fibroin as Biocompatible and Bioresorbable Enzyme Immobilization Matrix for Screen‐Printed Amperometric Glucose Biosensors - Kevin A. Janus; Stefan Achtsnicht; Benedetta Isella; Alexander Kopp; Koichiro Miyamoto; Tatsuo Yoshinobu; Michael Keusgen; Michael J. Schöning (Advanced Sensor Research)
Abstract Silk‐fibroin is utilized as a biocompatible and bioresorbable enzyme immobilization matrix and exemplarily demonstrated for a screen‐printed amperometric glucose biosensor. The silk‐fibroin is derived from the silkworm Bombyx mori. The enzyme immobilization matrix consisting of silk‐fibroin, together with glucose oxidase from Aspergillus niger, is applied to a screen‐printed carbon‐based, biocompatible, and biodegradable working electrode on a flexible silk‐fibroin substrate. The biosensor is characterized electrochemically at physiological glucose concentrations in the range from 0.5 to 10 mm. The results are compared to a “conventional” glucose biosensor, also fabricated on a flexible silk‐fibroin substrate, however utilizing a laboratory standard enzyme immobilization matrix based on bovine serum albumin and glutaraldehyde. Furthermore, the influence of pH (pH 5.5 to pH 8.0) and temperature variations (21 to 70 °C) on these two different immobilization matrices are studied.